Impact of Smoking and Smoking Cessation on Periodontal Health: A Review - Goel, Khushboo; Gorkhali, Ranjita Shrestha; Pradhan, Shaili; Gupta, Sujaya (Journal of Nepalese Society of Periodontology and Oral Implantology, 2017)
Tobacco use persists as a chronic global public health concern. The deadly habit affects almost all organs of the body including the oral and periodontal structures. Smoking is established as one of the major preventable etiological risk factors for the initiation and progression of periodontitis. The habit dependence typically requires a continuous assessment and repeated intervention. Emerging evidence has suggested the benefit of smoking cessation on periodontal health that trends for greater probing depth reductions and a favorable response to treatment outcomes. The dental settings are now increasingly being recognized as a place to target patients to quit or even prevent the initiation of smoking habit. The dental practitioner and the periodontal specialist may, therefore play a pivotal role by the inclusion of smoking cessation programs in their daily practice and reduce the major risk involving oral tissues and the systemic health. This review addresses the impact of smoking on periodontal tissues, the effect of smoking cessation protocols to improve periodontal health and the role of professionals in cessation.